The dynamics of genome size and GC contents evolution in genus Nicotiana - Hussain,Z. (2023)
Abstract Hybridization and Polyploidization are most common of the phenomenon observed in plants, especially in the genus Nicotiana leading to the duplication of genome. Although genomic changes associated with these events has been studied at various levels but the genome size and GC content variation is less understood because of absence of sufficient genomic data. In this study the flow cytometry technique was used to uncover the genome size and GC contents of 46 Nicotiana species and we compared the genomic changes associated with the hybridization events along evolutionary time scale. The genome size among Nicotiana species varied between 3.28 pg and 11.88 pg whereas GC contents varied between 37.22% and 51.25%. The tetraploid species in genus Nicotiana including section Polydiclae, Repandae, Nicotiana, Rustica and Sauveolentes revealed both up and downsizing in their genome sizes when compared to the sum of genomes of their ancestral species. The genome sizes of three homoploid hybrids were found near their ancestral species. Loss of large genome sequence was observed in the evolutionary more aged species (>10 Myr) as compared to the recently evolved one’s (<0.2 Myr). The GC contents were found homogenous with a mean difference of 2.46% among the Nicotiana species. It is concluded that genome size change appeared in either direction whereas the GC contents were found more homogenous in genus Nicotiana.